The impact of the Turkish intervention in northern Syria and its repercussions on the Syrian-Turkish relations and the stability of the region - بلال ماريا; عفيف يوسف حيدر; شادي سمير شهيلة (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The research discusses the impact of the Turkish intervention in northern Syria and its repercussions on the Syrian-Turkish relations and the stability of the region during the period between (2011-2020) and the extent of its impact on the Syrian-Turkish relations in the northern Syrian region in particular, and analyzes the weaknesses and strengths in the Turkish position with regard to the Kurds. The research relied on the analytical descriptive approach and the historical approach. The research reached a set of results, namely: the existence of a correlation between the internal and external factors, which allowed Turkey to play a new role in northern Syria, which in turn affected the relations between the two countries. The results also confirmed the existence of a correlation between the outbreak of the war on Syria in 2011, and the divergence of relations between them, which in turn led to the entry of Turkish forces into northern Syria. He made this problem an obstacle to any development in the Syrian-Turkish relations.